PEMILIHAN METODE KONTRASEPSI BERDASARKAN STATUS PARITAS WANITA USIA SUBUR (WUS) - hardjito, koekoeh; liawati, sisca; yani, erna rahma (Universitas Nusantara PGRI Kediri, 2019)
The selection of contraception methods is an important part in implementation family planning program that is to limit the number of births from every woman of childbearing age with birth controlthat 2 children areenough. One of the factors that influence the selection of contraceptive methods is parity of childbearing age. The purpose of this research was to determined the relationship between parity with the selection of contraceptive methods in women of childbearing age. Analytic research designed with a cross-sectional approach. Population in the research was all data of women of childbearing age the active participants of family planning January - December 2017 period. Sampling using simple random sampling technique amounting to 165. Based on the statistical test by using chi-squareαat = 0,05 obtained p-value = 0,000 <0,05 so it can be concluded that there was a significant correlation between parity with the choice of contraception method on women of childbearing age.